Впровадження оцінок відстаней у класифікації зображень - Дебре, В. С. (ХНУРЕ, 2023)
The presented research materials concern the application of distance assessment to the reference class in image classification. Experimental results confirm a significant performance gain for the developed classification methods.
Keywords: класифікація зображень; швидкодія аналізу; оцінка відстані